"Once Was Blind but Now Can See": Modernity and the Social Sciences1. Issue 2 (10th June 2013) - Seth, Sanjay
Abstract : This article asks a series of very direct, if not simple, questions. How, and why, is it that we assume that modern knowledge is universal, despite its European genealogy and its historically recent provenance? What warrant do we have for considering this knowledge superior to the premodern knowledges of the West and the autochthonous knowledges of the non‐West? Are we, in short, right to assume that modern Western knowledge transcends the circumstances of its historical and geographical emergence and thus that the social sciences are "true" for everyone—even though to do so is to privilege the modern and the Western over the premodern and the non‐Western? In addressing these questions, this essay highlights the exclusions—of gods and spirits, and of nature—that have gone into the constitution of the concept of "the social, " a taken‐for‐granted object which provides the ground and the subject matter for the social sciences.